THE EFFECT OF GOLD NANOPARTICLES SYNTHESIZED BY SODIUM CITRATE AND FUNCTIONALIZED WITH ANTICANCER AND NATURAL COMPOUNDS ON CANCER CELL LINES: DEDICATED TO THE MEMORY OF ASSOCIATED PROFESSOR MARIUS IULIU SALAJAN (1952-2004) - UJICA, Madalina Anca; MANG, Ionel; HOROVITZ, Ossi; SORITAU, Olga; TOMOAIA, Gheorghe; MOCANU, Aurora; BENEA, Horea-Rares-Ciprian; RAISCHI, Viorica; VARHELYI, Csaba; BORODI, George; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Natural compounds, such as trans-resveratrol, R, piperine, P, and icariin, Ic, have antioxidant and anti-inflammatory properties, and potential anticancer activity. Gold nanoparticles, GNPs, are biocompatible and can be used as carriers for biomolecule delivery, improving their performance at a small dose. The aim of the present study was to synthesize GNPs with sodium citrate, noted GNP_C (or GNP-C), and enhancing their stability and anticancer activity by functionalization with R, P, Ic, asparagine, A, and doxorubicin, D, as a standard drug. The obtained GNPs as cores, loading selected biomolecules, adsorbed on their surface as shells, were characterized by various methods, UV-Vis spectroscopy, XRD, AFM, TEM, and particle size analysis. The anticancer activity of functionalized GNP_C was evaluated using MTT assay in four human cell lines: breast cancer, MDA-MB-231 and MCF-7 cell lines, tumor stem cells (isolated from glioblastoma), a GM1 cell line, and a normal (healthy) stem cell line derived from a dental follicle, DF. GNP_C functionalized with R, P or Ic exhibited an anticancer activity comparable to GNP_C functionalized with doxorubicin for low concentrations in gold and in natural compounds, thus reducing side effects of anticancer drug. These promising results need further examination using various cell lines and animal models, to clinical applications.